2021
DOI: 10.3390/foods10040819
|View full text |Cite
|
Sign up to set email alerts
|

Application of Broccoli Leaf Powder in Gluten-Free Bread: An Innovative Approach to Improve Its Bioactive Potential and Technological Quality

Abstract: In comparison to conventional bread, gluten-free bread (GF) shows many post-baking defects and a lower nutritional and functional value. Although broccoli leaves are perceived as waste products, they are characterised by a high content of nutrients and bioactive compounds. The present study evaluated the nutritional value, technological quality, antioxidant properties, and inhibitory activity against the formation of advanced glycation end-products (AGEs) of GF enriched with broccoli leaf powder (BLP). Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 54 publications
(57 reference statements)
0
19
1
Order By: Relevance
“…Some artificial ingredients could alter human enzymes and lipids and may cause carcinogenic effects [11]. As a result, recent studies have been conducted to replace artificial ingredients with natural ingredients derived from agricultural waste [12]. The growing interest in natural antioxidant, antitumor, and antimicrobial substances has provided new insights into plant by-products as a source of these bioactive substances [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some artificial ingredients could alter human enzymes and lipids and may cause carcinogenic effects [11]. As a result, recent studies have been conducted to replace artificial ingredients with natural ingredients derived from agricultural waste [12]. The growing interest in natural antioxidant, antitumor, and antimicrobial substances has provided new insights into plant by-products as a source of these bioactive substances [13].…”
Section: Introductionmentioning
confidence: 99%
“…1 , the cakes C1, C2, C3, and C4 presented aeration in their masses, and this aeration may be related: (I) with the use of chemical yeast, as mentioned in the cake preparation method [ 37 ]; (II) with the stirring time that the eggs remain. Because the eggs are great aeration agents, the longer the stirring time, the smaller the size of the air bubbles, and the more the amount present in the dough surrounded by the egg proteins [ 38 ]; (III) owing to the protein content presented in the pasta, it is therefore possible that these proteins present can mimic the stable network that is formed when gluten is present, similar to the study by Krupa-Kozak et al When using broccoli flour to make gluten-free bread, they realized that the bread exhibited aeration and could be due to the proteins from the broccoli flour [ 39 ]. It is not possible to determine the situation that was the case in this study, as cake C1 also presented aeration and was not fortified with green coffee bean flour; however, it is likely that in the case of cakes C2, C3, and C4, the flour was responsible because the studies of Guglielmetti et al, Littardi et al, and Rios et al, presented breads with aerated doughs [ 40 – 42 ].…”
Section: Resultsmentioning
confidence: 95%
“…In addition to hemp flour and hemp seed ( Cannabis sativa ) press cakes, which are a by-product of hemp oilseed production, beans and their by-products, vegetables and their by-products, mushrooms and groundnuts, as well as other seeds, such as flaxseed, are also often used to enhance the nutritional value of gluten-containing and gluten-free breads [ 12 , 13 , 14 , 15 , 16 , 17 ]. Vegetables and their by-products are usually used to enhance the amount of bioactive compounds and mineral content as well as to add fibre.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables and their by-products are usually used to enhance the amount of bioactive compounds and mineral content as well as to add fibre. A study on the addition of broccoli leaf powder to gluten-free bread showed that the overall nutritional value, as well as technological parameters such as bake loss, can be improved by the addition of non-traditional bread ingredients [ 15 ]. Other studies highlighted that the addition of ground nuts can improve the sensory properties of breads, but technological parameters, such as bread volume, are often adversely affected [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%